2016
DOI: 10.1007/s10964-016-0596-x
|View full text |Cite
|
Sign up to set email alerts
|

When Mothers and Fathers Are Seen as Disproportionately Valuing Achievements: Implications for Adjustment Among Upper Middle Class Youth

Abstract: High achievement expectations and academic pressure from parents have been implicated in rising levels of stress and reduced well-being among adolescents. In this study of affluent, middle-school youth, we examined how perceptions of parents' emphasis on achievement (relative to prosocial behavior) influenced youth's psychological adjustment and school performance, and examined perceived parental criticism as a possible moderator of this association. The data were collected from 506 (50% female) middle school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 103 publications
5
29
1
4
Order By: Relevance
“…On more detailed inspection, however, the findings of this study differ from those of earlier studies involving non-gifted samples. Unlike the other studies, which found a positive relationship between parental performance goals and negative emotions such as academic stress [17], in this study parental performance did not predict most of negative achievement emotions. Instead, parental performance goals seemed to decrease the positive achievement emotions of gifted students.…”
Section: Discussioncontrasting
confidence: 99%
“…On more detailed inspection, however, the findings of this study differ from those of earlier studies involving non-gifted samples. Unlike the other studies, which found a positive relationship between parental performance goals and negative emotions such as academic stress [17], in this study parental performance did not predict most of negative achievement emotions. Instead, parental performance goals seemed to decrease the positive achievement emotions of gifted students.…”
Section: Discussioncontrasting
confidence: 99%
“…Our specific question was how SES, not stress, is shaping cognitive control. (Ansary, McMahon, & Luthar, 2017;Ciciolla, Curlee, Karageorge, & Luthar, 2017;Coren & Luthar, 2014;Luthar, Small, & Ciciolla, 2018). In our sample, children who did experience negative or traumatic experiences as measured by the LEC were scattered across the SES continuum.…”
Section: Discussionmentioning
confidence: 93%
“…Other data have repeatedly shown that some stressful life events are more common in high SES homes. Extensive research from Luthar and colleagues has demonstrated that high SES homes and schools impose stressors for unrealistic achievement that result in high rates of internalizing disorders and substance abuse by early adolescence (Ansary, McMahon, & Luthar, ; Ciciolla, Curlee, Karageorge, & Luthar, ; Coren & Luthar, ; Luthar, Small, & Ciciolla, ). In our sample, children who did experience negative or traumatic experiences as measured by the LEC were scattered across the SES continuum.…”
Section: Discussionmentioning
confidence: 99%
“…Every parent is different in applying to parent and their behavior towards children. It depends on the attitude that they are learning in a nurturing and educating children, among others, the existence of initial experience with children, the knowledge of how to best treat the child either in democratic or authoritarian, permissive (Bradley et al, 2017;Ciciolla et al, 2017;Czymoniewicz-Klippel et al, 2019;Dicé et al, 2017). Most parents apply authoritarian parenting which authoritarian parenting harms children.…”
Section: Discussionmentioning
confidence: 99%